The Effects of World Heritage Sites on Domestic Tourism: A Spatial Interaction Model for Italy - Roberto Patuelli; Maurizio Mussoni; Guido Candela (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
Culture is gaining increasing importance in the modern tourism industry, and represents a significant force of attraction for tourists (both domestic and international). Cultural tourism allows destinations and regions to expand their customer base, diversify their offer, extend the stay of the tourist, and reduce seasonality. Great efforts are made, by national governments and regions, in order to obtain official designation regarding the relevance of their historical/cultural attractions, for example through UNESCO's World Heritage Sites (WHS) list. Such an aspect seems particularly relevant for a country like Italy, which has a high number of entries in the WHS list, and where regions take an active role in promoting tourism. Using an 11-year panel of domestic tourism flows, we investigate the importance of the regional endowment in terms of WHS from two perspectives: (a) by separately estimating the effects, on tourism flows, of WHS located in the residence region of tourists and in the destination region; and (b) by taking into account potential spatial substitution/complementarity effects between regions due to their WHS endowment. Finally, a sensitivity analysis is offered to evaluate the spatial extent of the latter.
Keywords: C23; L83; R12; Z10; 330